Evaluasi Status Gizi Siswa SDN 1 Sikunang, Wonosobo, melalui pengukuran Antropometri dengan WHO AnthroPlus - Wulan May Kusuma Dewi; Nazrul Effendy; Muhammad Ismail Al Birru (Universitas Muhammadiyah Surakarta, 2024)
Students of SDN 1 Sikunang, Wonosobo habitually consume unhealthy foods that affect their nutritional status, which is intervened by their lifestyle, parenting, and the unhealthy food condition of the school canteen. It is proven by 30.3% of students in grades 4-6 have abnormal nutritional status. Therefore, it requires an assessment of nutritional status by anthropometric measurement of body mass index based on age to all students. This community service aims to measure the level of nutritional status of students at SDN 1 Sikunang and can be implemented by the school in the long term. A total of 114 students were measured anthropometrically using analog weight scales and microtoise to determine body mass index. The data was analyzed together with the age data of each student utilizing WHO AnthroPlus to determine the level of IMT/U nutritional status. From this activity, 3.5% of students were found to have severely thinness, 9.7% of students with thinness, 73.7% with normal nutrition, 4.4% with overweight, and 3.5% as obese. These results indicate that 26.3% of students at SDN 1 Sikunang are still classified as having abnormal nutritional status. It is recommended that the nutritional status of these students be routinely monitored by the health unit of SDN 1 Sikunang and informed to parents. In addition, it is recommended that the school commits to implementing a healthy canteen and educating students and parents about balanced nutrition and healthy foods.